Menguji Lebih Dalam Dampak Dimensi Service Quality Perguruan Tinggi pada Satisfaction, Word of Mouth dan Service Switching - Muhammad Johan Widikusyanto (Sains: Jurnal Manajemen dan Bisnis, 2022)
Universities have a big role as well as a responsibility to improve the quality of human resources. However, competition between higher education providers is an obstacle to the creation of quality human resources. Having a competitive advantage is a must in facing competition as well as carrying out their roles and responsibilities. The purpose of this study is to develop and test a model that is able to explain the factors forming competitive advantage and their impact on Service Switching and Word of Mouth. Data were collected using surveys and analyzed using SEM. Questionnaires were distributed to students from ten public and private universities in five areas of Banten with a total of 1000 students as respondents. The test results show Tangible to be the most influential factor on Satisfaction. Meanwhile, Assurance is one of the service quality factors that has the greatest influence on WOM. However, of all the constructs studied, satisfaction is the factor that has the greatest influence on WOM. Next, Assurance is one of the most influential service quality factors on HEI Switching.